Post-Transcriptional Maturation of the S Receptor Kinase of Brassica Correlates with Co-Expression of the S-Locus Glycoprotein in the Stigmas of Two Brassica Strains and in Transgenic Tobacco Plants - Dixit, Ram (American Society of Plant Physiologists, 2000)
The S-locus-encoded S receptor kinase (SRK) is an intrinsic plasma membrane protein that is viewed as the primary stigma determinant of specificity in the self-incompatibility response of Brassica spp. We analyzed two self-compatible mutant strains that express low levels of the S-locus glycoprotein (SLG), a cell wall-localized protein also encoded at the S locus that is coordinately expressed with SRK. We found that mutant stigmas synthesized wild-type levels of SRK transcripts but failed to produce SRK protein at any of the developmental stages analyzed. Furthermore, SRK was shown to form aberrant high-molecular mass aggregates when expressed alone in transgenic tobacco (Nicotiana tabacum) plants. This aggregation was prevented in tobacco plants that co-expressed SRK and SLG, but not in tobacco plants that co-expressed SRK and SLR1, an SLG-related secreted protein not encoded at the S locus. In analyses of protein extracts under reducing and non-reducing conditions, evidence of intermolecular association was obtained only for SLG, a fraction of which formed disulfide-linked oligomers and was membrane associated. The data indicate that, at least in plants carrying the S haplotypes we analyzed, SRK is an inherently unstable protein and that SLG facilitates its accumulation to physiologically relevant levels in Brassica stigmas.